Efficient or Opportunistic: An Empirical Test of Managerial Discretion of Islamic Banking in Reporting The Earnings - Abbas, Ahmad; Triani, Neks; Rayyani, Wa Ode; Radwan, Maha (Economica: Jurnal Ekonomi Islam, 2021)
Managers are responsible for the decision-making related to financial information. They make financial reporting incentives to manage financial data, including the earnings. Banks under Islamic principles seem to affect the probability of problematic managerial behavior in determining earnings. This study determines whether Islamic banking managers' discretion in reporting earnings is efficient or opportunistic. The sample of this study was Islamic commercial banks in Indonesia. The data was obtained from Bank Indonesia and Financial Services Authority. Their financial statements from 2010 to 2016 were analyzed using Moderated Regression Analysis. As reported by the analysis results, managers in Islamic banking are efficient in their discretion while reporting their earnings. Managers tend to level down their earnings when the profitability is exceptionally high at the current earning and movie it to the future earning making the profitability of Islamic banks seem stable.